Internationalization in Canadian Higher Education: A Case Study of the Gap between Official Discourses and On-the-Ground Realities - Larsen, Marianne A. (Canadian Journal of Higher Education, 2015)
This case study about one university’s internationalization initiative, known as North Goes South, provides a nuanced and finely grained understanding of what internationalization looks like in practice. The study was guided by a desire to probe the perceived impact of a Canadian–East African internationalization initiative on students, faculty, and Tanzanian community members. The article begins with a brief review of the literature on internationalization and higher education in Canada. The rationale for using a case-study methodology is presented, along with the background and context of the case. Following an outline of the research methods, the study results are reviewed to show the complex and contradictory ways in which this internationalization initiative played out in one higher education setting, pointing to the gap between official discourses of internationalization and on-the-ground realities.